Vigilância do desenvolvimento na caderneta de saúde da criança - França, Daniele Beltrão Lucena de (2020)
Introduction: Child development surveillance provides continuous care at every stage of life and the child's health handbook is an ideal instrument for this monitoring, due to its potential to promote longitudinal care. Objective: To investigate child development surveillance actions registered in the Child Health Handbook. Methodological path: A descriptive, cross-sectional study, conducted with the analysis of 424 books of children under three years old, registered at the Family Health Units in the city of João Pessoa - PB, from May to November 2019. The data were analyzed using the statistical programs R and PSPP, with descriptive and inferential analysis, considering a tolerable sample error of 5%. The research was approved by the Research Ethics Committee of the Center for Health Sciences of the Federal University of Paraíba, under opinion number 3.156.449 and registered by the CAAE: 97362718.1.0000.5188. Results: The items with the best records were age (67.7%) and weight (70.3%) on the record sheet; date and time of birth (67.5%) and weight (67.5%) at birth. However, weaknesses were identified in completing the development items (26.7%); maternal clinical complications (0.2%); prenatal and maternity serologies (4.0% each); red reflex test (10.4%) and head circumference curve (9.7%). In the regressions, the age of the mother/caregiver, number of children, years of schooling, income, age and sex of the child were associated with the outcomes - record of growth and development. The number of children work at home, the score of the child and the woman and the child's age showed a statistically significant association. Conclusion: The use of the booklet for monitoring child development is below expectations, compromising the integrality of child care and the possibility of early identification of developmental problems.